CONSERVAÇÃO DE PIMENTÕES (Capsicum annuum L.) ATRAVÉS DAS RADIAÇÕES GAMA DO COBALTO-60 - Wiendl, Frederico Maximiliano; Arthur, Valter; Wiendl, Toni Andreas (REVISTA DE AGRICULTURA, 2015)
CONSERVAÇÃO DE PIMENTÕES (Capsicum annuum L.) ATRAVÉS DAS RADIAÇÕES GAMA DO COBALTO-60